(untitled) (Palimpsesto, 2021)
This article presents a bibliographic balance of some of the trends in the analysis of inter-ethnic relations from the review of approximately thirty academic documents published between 1995 and 2015 in indexed databases, university repositories and academic institutions, mainly from Colombia, Caribbean and Latin America. The documentary corpus was systematized in a qualitative data analysis computer program, through the creation of categories-codes that classified the articles by themes, countries, disciplinary perspectives and time periods. We identify some of the trends in the study of inter-ethnic relations and categorize them into three key themes: miscegenation, marital relationships and discrimination. Based on the balance, we propose routes of inquiry to understand inter-ethnic relations and promote their use as an analytical category.